Protein Blend and Casein Supplementations before Inactive Phase Similarly Activate Mechanistic Target of Rapamycin Signaling in Rat Skeletal Muscle - Vieira, Tales Sambrano [UNESP]; Pinto, Ana P.; Batitucci, Gabriela [UNESP]; Rocha, Alisson L.; Filho, Hugo T.; Goncalves, Dawit A.; Silva, Adelino Sanchez R. da; Freitas, Ellen Cristini de [UNESP] (Wolters Kluwer Medknow Publications, 2020)
During overnight sleep, the longest postabsorptive and inactive phase of the day causes protein catabolism and loss. However, the daytime ingestion of dairy proteins has been shown to stimulate muscle protein synthesis and growth. This study compared the effects of pre-sleep supplementation of a protein blend (PB) composed of micellar casein (MCa) and whey protein (1:1) versus isolate MCa on the plasma levels of branched-chain amino acids (BCAAs) and the activation of the mechanistic target of rapamycin (mTOR) signaling, a critical intracellular pathway involved in the regulation of muscle protein synthesis. After 10 h of fasting during the active phase, rats were fed with a single dose of PB or MCa (5.6 g protein/kg of body mass) by gavage, and samples of blood and gastrocnemius muscle were collected at 30, 90, and 450 min. PB and MCa supplementations induced an increase (similar to 3-fold, P < 0.001) of plasma BCAAs at 30 and 90 min. Most importantly, the stimulatory phosphorylation levels of mTOR and its downstream target p70 ribosomal protein S6 kinase (p70S6K) were similarly higher (similar to 2.5-fold, P < 0.001) 30 and 90 min after MCa and PB. Plasma levels of leucine, isoleucine, valine, and overall BCAAs were correlated with the activation of mTOR (P < 0.001) and p70S6K (P < 0.001). MCa and PB supplementations before the inactive phase of rats resulted in an anabolic milieu in the skeletal muscle by inducing a transient increase in plasma BCAAs and a similar activation of the mTOR/p70S6K axis.
Keywords: Micellar casein; mTOR signaling pathway; protein supplementation; protein synthesis; skeletal muscle; whey protein